Efektivitas terapi gym ball sebagai solusi nyeri punggung bawah di trimester akhir kehamilan - Rohila, Titin; Besmaya, Beniqna Maharani; Fara, Yetty Dwi; Agustina, Rika; Ayu, Juwita Jesri (Poltekkes Kemenkes Aceh, 2025)
Background: Lower back pain is a common issue during pregnancy, especially in the third trimester, affecting approximately 50%-80% of pregnant women. This discomfort can arise from excessive bending, prolonged walking without rest, and frequent heavy lifting.Objective: This study aims to determine the effect of gym ball therapy on lower back pain among third-trimester pregnant women at Posyandu Desa Pardasuka, under the jurisdiction of Puskesmas Katibung, South Lampung Regency.Methods: The study used a pre-experimental method with a one-group pretest-posttest design. It was conducted in July 2024 at Posyandu Desa Pardasuka, involving a population of all third-trimester pregnant women (15 individuals), selected through purposive sampling. Data collection consisted of several stages, starting with a pre-test where the researcher obtained research permissions, provided informed consent, and measured the intensity of lower back pain using a Numerical Rating Scale (NRS).Results: The results showed that the average lower back pain score among third-trimester pregnant women before gym ball therapy was 5,60, with a standard deviation (SD) of 0,507. After the therapy, the average score significantly decreased to 2,93, with an SD of 0,258. Statistical analysis using the t-test indicated a significant reduction in pain, with a p-value of 0,000 (p < 0,05). This demonstrates that gym ball therapy is effective in reducing lower back pain in third-trimester pregnant women.Conclusion: Gym ball therapy is effective in reducing lower back pain among third-trimester pregnant women. Pregnant women are encouraged to perform this therapy regularly under the guidance of healthcare professionals.